"PORTRAIT IS A MIRROR OF THE ARTIST'S SOUL" - Luiza Albastova (Scholar Express Journal, 2022)
The portrait is perhaps one of the most attractive genres of painting and at the same time ambiguous. The word "portrait" came from the Old French word "pourtrait" which means the image of line to line. In Russian, the word portrait means"similar." It is the portrait that provides the opportunity to talk about the image of a person, allows you to get close to the worldview of personality in various eras. It is interesting to recall a little history of the portrait genre. Especially female portraits of great artists are so unique, you can notice and trace the features of life, clothes of that time. There may be different eras, portrait schools, directions, but in the foreground there is always female beauty and attractiveness. The ideals of beauty at all times were different, but such as Leonardo da Vinci, Titian, Daly-all make it clear to us that in practice a female ideal simply cannot exist. The ceremonial portrait is no less attractive, but this is a less common phenomenon in modern art. Art history introduced us to examples of wonderful works that belonged to this species. It is enough to name the names of D. Velasquez, A. Van Dyck, D. Levitsky, P. Rubens. During the evolution of the portrait there appeared stable portrait forms which represent various ways of comprehending man in the history of culture: "Portrait-likeness" the main priority of which is the transmission of physical similarity to the portraitised; " Portrait-status "where the dominant image is the image of a person in his connections with society; "Portrait-mask" hiding the personality behind the variability of the cultural pattern. "Portrait - social type" where the emphasis from the unique, individual is transferred to the transfer of common features of the individual's belonging to a certain social niche; "Portrait-idea" expressing the author's concept of the artist, and "Portrait-soul" addressed to the transmission of the inner world of the individual. The portrait genre has a unique artistic language that makes it possible to comprehend many people. Art widely uses the conventional language of cultural stereotypes of the perception of a given person by others, and highlighting or hyperbolizing some features of a person's appearance helps identify the image with a specific personality. Nowadays, the portrait is loved by artists and spectators. The portrait as a genre of fine art has always attracted me, you can express the mood, the soul of the person. By depicting people, I look for people in accordance with my idea of human beauty, eyes, hands through which I look at the world. It is interesting to show the essence of a person from the inside. The model can be talked, put in other conditions. Every person has beauty. You have to be able to see it. It is interesting to overcome a difficult one. Write a graceful smile, a strange look, a complex color glowing from the inside, which is a big work
Keywords: Fine arts; portrait; modern art